1992
DOI: 10.1016/0741-5214(92)70021-c
|View full text |Cite
|
Sign up to set email alerts
|

Reversed vein graft stenosis: Early diagnosis and management

Abstract: Conscientious surveillance ofintrainguinal bypass grafts is mandatory to detect vein graft stenoses, which, ifuncorrected, can lead to graft occlusion. It is now widely accepted that noninvasive vascular laboratory studies are the best way to detect these lesions. However, controversy still exists over treatment, specifically whether balloon angioplasty is an acceptable substitute for surgery (patch angioplasty or short jump grafts) in the treatment ofthese lesions. We have always favored balloon angioplasty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(36 citation statements)
references
References 13 publications
(3 reference statements)
1
34
0
1
Order By: Relevance
“…On the basis of these findings we speculate in accordance with Davies et al 20 and Marin et al 10 that diabetes affects venous physiology and may contribute to graft failure. Intimal hyperplasia, 10,14,15 preexisting disease, 18,19 and thick or calcified walls 10 are among the numer- ous factors that increase the risk of intragraft lesions. Our results also validate the usefulness of experimentally induced diabetes in animals as a model for further study to clarify the fate of the diabetic venous wall when used as a graft in patients with peripheral vascular disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of these findings we speculate in accordance with Davies et al 20 and Marin et al 10 that diabetes affects venous physiology and may contribute to graft failure. Intimal hyperplasia, 10,14,15 preexisting disease, 18,19 and thick or calcified walls 10 are among the numer- ous factors that increase the risk of intragraft lesions. Our results also validate the usefulness of experimentally induced diabetes in animals as a model for further study to clarify the fate of the diabetic venous wall when used as a graft in patients with peripheral vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the vascular endothelium occur early in the course of diabetes and have been implicated in the onset of diabetic complications. 11,12 Thirty percent of peripheral bypass grafts develop stenosis within 1 year after implantation 13 and several studies have shown that these lesions are due to intimal hyperplasia, 14,15 which is the consistent response of vein graft inserted into arterial circulation. The cause of this response in diabetic patients is unclear, but it has been suggested that hyperglycemia, through nonenzymatic glycocylation endproducts, which can modulate cellular responses, alters venous structure and vascular responses.…”
Section: Introductionmentioning
confidence: 99%
“…While long term patency and tory the distal end was divided and 1-2 cm immediately survival are good for ITA grafts the prognosis for SV placed in physiological salt solution. grafts is less promising [13,14]. This has led to the search The vessel segments were immediately transferred to the for other suitable conduit vessels.…”
Section: Introductionmentioning
confidence: 99%
“…This reduced patency has been largely attributed to compliance mismatch between the AVG and the native artery to which it is grafted [18,232,233]. Veins are inherently less compliant than arteries [234] and become even less compliant upon abruptly exposed arterialization [235].…”
Section: Changes In Mechanical Properties Of Vein Grafts Due To Artermentioning
confidence: 99%